2018
DOI: 10.1177/2156759x19867332
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between the Multicultural Self-Efficacy, Empathy, and Training of School Counselors and Their Knowledge and Skills Supporting Students Experiencing Homelessness

Abstract: Homelessness remains a national concern impacting the lives of many individuals and families. We examined the relationships among participating school counselors’ self-reported multicultural self-efficacy, empathy, training, and knowledge and skills supporting students experiencing homelessness. Results of a three-stage hierarchical multiple regression indicated that the most significant predictors of school counselors’ knowledge and skills were training and multicultural self-efficacy, respectively. We presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Some participants noted broaching the topic of homelessness as a challenge in identifying these students and their respective needs. Stigmas associated with homelessness are often the prime factor in students and families choosing to not disclose their circumstances to school counselors, liaisons, or other stakeholders (Camp et al, 2018; Canfield, 2014; Havlik et al, 2020). Previous literature has also indicated that several school counselors in training perceived broaching social determinants of health (SDOH) needs, such as homelessness, as beyond their scope of practice (Gantt et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Some participants noted broaching the topic of homelessness as a challenge in identifying these students and their respective needs. Stigmas associated with homelessness are often the prime factor in students and families choosing to not disclose their circumstances to school counselors, liaisons, or other stakeholders (Camp et al, 2018; Canfield, 2014; Havlik et al, 2020). Previous literature has also indicated that several school counselors in training perceived broaching social determinants of health (SDOH) needs, such as homelessness, as beyond their scope of practice (Gantt et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that their finding supports the assumption of SCT that multicultural training experience, particularly based on direct mastery, helps to develop multicultural counselling selfefficacy. In a more recent study, training significantly contributed to trainees' multicultural counselling self-efficacy in helping clients experiencing homelessness (Camp et al, 2019). A positive relationship between the two variables was also found in non-counselling literature.…”
Section: Discussionmentioning
confidence: 79%
“…Matthews et al (2018) examined MCSE in practicing counselors, reporting that their sample had "strong self-efficacy" but did not report specific mean scores on the MCSE-RD. Other studies examined MCSE in school counselors but used other instruments, so comparisons are cautioned (Camp et al, 2019;Holcomb-McCoy et al, 2008).…”
Section: Discussionmentioning
confidence: 99%